Scattering of acoustoelectric waves on a cylindrical inhomogeneity in the transversely isotropic piezoelectric medium - Levin, Valery; Michelitsch, Thomas (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2001)
Scattering of acoustoelectric waves on an inhomogeneity is studied. The scatterer is a circular continuous piezoelectric cylinder (fiber) embedded in the piezoelectric transversely isotropic medium. Expressions are found for scattering amplitudes and total cross-sections of the three acoustoelectric waves propagating in the direction normal to the fiber axis. In the long-wave limit these expressions are abtained explicitly.